Control of Post Prandial Blood Sugar Among the Treatment Patterns for Type 2 Diabetic Mellitus: A Retrospective Study - Velraj, Malarkodi; Ragesh, G.; Prasad, Poripiraddy Satya (Indian Journal of Pharmacy Practice)
Objective: The study mainly focused on retrospective comparison between the various treatments alternatives for good control of post prandial blood sugar in Type-2 diabetic patients. Methods: A Retrospective study was done in patients with type 2 diabetes mellitus. All the in-patients either gender, of age between 18 to 80 years were included in the study. Patients with known surgical histories, known and suspected cases of allergies and pregnant woman’s were excluded from this study. Totally 120 patients was included. Result: The post- prandial blood glucose results showed that significant reduction in all groups after 3rd, 6th and 18th month of treatment as compared to first reading. When assessment between Group-A (Metformin+Acarbose) and B (Metformin+Glimepiride) express that Metformin+Acarbose (Group-A) 176.16 ± 0.62 have a better reduction in PPBS than Metformin+Glimepiride (Group-B) 190.58 ± 1.7. Conclusion: Over all, the study concludes that a combination of Metformin and Sitagliptin have a greater impact on control of post-prandial blood sugar compared to other two combinations.
Keywords: Post prandial blood glucose; Diabetes mellitus; Metformin; Glimepiride and Acarbose